INOVASI LIGHT GELATO KELOR UNTUK TAMBAHAN TERAPI DAN PREVENTIF STUNTING - Abella , Maria Elvianita; Harismagita , Lalu Alan; Alwi, Andi Siti Fatimah; Majidi , Ahmad; Ramadoni , Siti Destika; Marjdun, Arhudawan; Novitadewi , Efi; Arifti , Lulu; Susanti , Susi; Hidayat, Tegar A. (Universitas Mataram, 2023)
Labuhan Haji Village is a village located in Labuhan Haji District, East Lombok Regency, NTB. This village is one of the villages where there are several infants and toddlers experiencing stunting. Based on data from the Posyandu of Labuhan Haji Village, there are more than 3 babies and toddlers aged 0-23 months and toddlers aged 24-59 months in every hamlet in Labuhan Haji Village experiencing stunting. The Community Service Group at Labuhan Haji Healthy Village, University of Mataram, through the Moringa Light Gelato Innovation work program, wants to help the community problems of Labuhan Haji Village, namely stunting, by providing education in the form of training in making Moringa Light Gelato. The Moringa Light Gelato Innovation is a work program from the Thematic KKN University of Mataram in Labuhan Haji Village which aims to provide information related to the processing of Moringa leaves (Moringa oleifera) as an additional therapy for stunting sufferers and stunting prevention efforts in Labuhan Haji Village and want to see the community's response to the work program which is conducted. Moringa leaves are functional food ingredients that contain protein, vitamins, minerals and antioxidants which have potential as a therapy and nutritional improvement for pregnant women and children who experience malnutrition. The work program of the Moringa Light Gelato Innovation as an additional therapy for stunting sufferers and stunting prevention is in demand by the community and has received a positive response which can be seen through wanting to make Moringa Light Gelato a healthy drink for daily consumption, as well as increasing interest in community entrepreneurship by wanting to make it Moringa Light Gelato as a business idea.